2019
DOI: 10.2478/mjhr-2019-0014
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of garlic (Allium sativum L.) germplasm

Abstract: A total of 25 garlic (Allium sativum L.) germplasm were collected from different location of Bangladesh and also from different countries of the world. Each germplasm was planted in each plot of 1m2 at the Allium Field Laboratory, Horticulture Farm, Bangladesh Agricultural University, Mymensingh. This study was conducted during October, 2010 to March, 2011 in the field, using randomized complete block design with three replications. All germplasm were characterized on number of leaves, height of plant, leaf le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
4
1
0
Order By: Relevance
“…It could be mainly attributed to the higher vegetative growth parameters like plant height, number of leaves per plant neck thickness and higher yield attributes viz., weight of bulb, bulb diameter, weight of clove, etc. The results of present findings are in agreement with the results reported by Salahuddin et al (2019), Mishra and Balaji (2017), Kowser et al (2018) and Bagchi et al (2020) in garlic genotypes.…”
Section: Yield and Yield Attributessupporting
confidence: 94%
See 2 more Smart Citations
“…It could be mainly attributed to the higher vegetative growth parameters like plant height, number of leaves per plant neck thickness and higher yield attributes viz., weight of bulb, bulb diameter, weight of clove, etc. The results of present findings are in agreement with the results reported by Salahuddin et al (2019), Mishra and Balaji (2017), Kowser et al (2018) and Bagchi et al (2020) in garlic genotypes.…”
Section: Yield and Yield Attributessupporting
confidence: 94%
“…The variation in number of leaves per plant in garlic genotypes might be due to the genetic potential of genotypes slightly modified by the new environment. The result of present findings are in close conformity with the earlier findings reported by Sharma et al (2015) and Salahuddin et al (2019) in garlic genotypes. The highest neck length at harvest was recorded in Phule Baswant (8.36 cm) whereas, the lowest recorded in G-119 (5.47 cm).…”
Section: Growth Parameterssupporting
confidence: 93%
See 1 more Smart Citation
“…Significant variation for number of leaves per plant was due to the difference between genotypes. Similar types of results were reported by researchers [16,17]. 2).…”
Section: Number Of Leaves Per Plantsupporting
confidence: 91%
“…Generally, the lowest number of cloves per bulb was recorded from medium to large sized cloves. Similar observations were made by different researchers [17,10,21] who reported that clove size had significant effects on the number of cloves per bulb.…”
Section: Number Of Cloves Per Bulbsupporting
confidence: 89%